Bacteria-targeting chitosan/carbon dots nanocomposite with membrane disruptive properties improve eradication rate of Helicobacter pylori. Issue 18 (12th December 2021) - Arif, Muhammad; Sharaf, Mohamed; Samreen,; Dong, Quanjiang; Wang, Lili; Chi, Zhe; Liu, Chen-Guang
Abstract: We designed a bacteria-targeting and membrane disrupting nanocomposite for successful antibiotic treatment of Helicobacter pylori ( H. pylori ) infections in the present study. The antibacterial nanocomposite was prepared from thiolated-ureido-chitosan (Cys-U-CS) and anionic poly (malic acid) (PMLA) via electrostatic interaction decorated with dual functional ammonium citrate carbon quantum dots (CDs). Cys-U-CS serves as a targeting building block for attaching antibacterial nanocomposite onto bacterial cell surface through Urel-mediated protein channel. Simultaneously, membrane disrupting CDs generate ROS and lyse the bacterial outer membrane, allowing antibiotics to enter the intracellular cytoplasm. As a result, Cys-U-CS/PMLA@CDs nanocomposite (UCPM-NPs) loaded with the antibiotic amoxicillin (AMX) not only effectively target and kill bacteria in vitro via Urel-mediated adhesion but also efficiently retain in the stomach where H. pylori reside, serving as an effective drug carrier for abrupt on-site release of AMX into the bacterial cytoplasm. Furthermore, since thiolated-chitosan has a mucoadhesive property, UCPM-NPs may adhere to the stomach mucus layer and pass through it swiftly. According to our results, bacterial targeting is crucial for guaranteeing successful antibiotic treatment. The bacteria targeting UCPM-NPs with membrane disruptive ability may establish a promising drug delivery system for the effective targeted delivery of antibiotics to treat H. pylori infections.